Molecular Characterization of Vibrio Parahaemolyticus Isolated from the Coasts of Port Klang and Lukut Located Along Peninsular Malaysia - Tanil, Gwendelynne Bulan (2004)
Vibrio parahaemolyticus is a halophilic bacterium frequently involved in seafood-associated gastroenteritis. In this study, V. parahaemolyticus was isolated from 14 (36.8%) of 40 seawater samples taken from coastal areas of three fishing villages namely Kuala Lukut in Negri Sembilan, Morib and Port Klang in Selangor. A total of 21 strains were studied for their antibiotic resistance, the occurrence of plasmids, and the presence or absence of a regulatory gene (toxR), and virulence genes (tdh and trh), the molecular fingerprint by enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) and pulsed field gel electrophoresis (PFGE) analysis. This study has shown that all strains were multiple resistant to three or more of the fourteen antibiotics tested with the MAR indices ranging from 0.29 to 0.57. The high MAR indices indicate that the strains originated from high-risk sources. Most strains were resistant to penicillin (100%), ampicillin (95.24%), carbenicillin (95.24%), erythromycin (95.24%) and bacitracin (71.43%). Some strains showed resistance to antibiotics such as cephalothin (28.57%), moxalactam (28.57%), kanamycin (19.05%), tetracycline (14.29%), nalidixic acid (9.52%), and gentamicin (9.52%). All strains were susceptible to streptomycin, norfloxacin and chloramphenicol. Seven strains harbored only one plasmid, 6 strains harbored two plasmids, and 8 strains had no plasmid. The plasmid size ranged from 2.6 to 35.8 MDa. All strains carried the toxR gene specific to V. parahaemolyticus while none had the tdh gene. However, one strain harbored the trh gene. Two molecular typing methods were used in this study to examine the genetic relatedness among the strains collected from different areas. In the analysis by the ERIC-PCR, primers ERIC 1R and ERIC 2 were used. In this analysis, 15 different ERIC profiles were observed, displaying a wide array of diversity among the strains; the strains could be differentiated into 2 clusters and 14 single isolates based on 70% similarity level of the dendogram constructed. In the PFGE method, Sfi I restriction enzyme was used. Cluster analysis of the PFGE profiles divided the strains into 4 clusters and 9 single isolates based on the 70% similarity level. However, this method suffered from substantial DNA degradation resulting in four untypeable strains. This study, demonstrated that the coastal seawater in Peninsular Malaysia is a potential source for pathogenic V. parahaemolyticus that can contaminate the seafood harvested from these areas.